Icnología de la Formación Sepulturas (Ordovícico) en el Espinazo del Diablo, Cordillera Oriental de Jujuy, Argentina (Ameghiniana, 2014)
Trace fossils of the Lower Ordovician Sepulturas Formation (Arenig) are analyzed and figured for the first time. The unit represents a marginal marine paleoenvironment (estuarine-deltaic), characterized by recurrent bioturbated wave rippled sandstone levels. High density / mid-diversity pasichnia dominates the ichnological association, being referred to the Cruziana ichnocoenosis. Higly variable paleoecological conditions along the unit characterizes the distribution of trace fossils as Cruziana furcifera dOrbigny, Cruziana isp., Dimorphichnus obliquus Seilacher, Diplichnites ísp., Monomorphichnus multilineatus Alpert, Monomorphichnus isp., Palaeophycus tubularis Hall, Thalassinoides ísp. and Skoliihos linearis Haldeman.